Kualitas Pelayanan Publik Melalui Pendekatan Model Demokrasi pada Era Otonomi Daerah - Achmad Nurmandi; Muhammad Lutfi; Zuly Qodir; Sumardi Sumardi (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2021)
This paper aims to analyze how regional autonomy policies can provide improving the quality and effectiveness of public services in accordance with the ideals of reform. Use descriptive analysis of the literature review. Effectiveness and benchmarks for the quality of public services largely determined by the substance of the existence of transparency and accountability through capacity good public communication, Management commitment to implementing Standard Operations More fair and democratic procedures, Then ensure the ability of the bureaucracy in provide public services and ensure public control in carrying out complaints on the fulfillment of their rights run optimally. Although on the other hand regional cooperation In the era of regional autonomy, the interests of certain elites and groups are still full of excitement. However does not mean ignoring community control as a control that is able to ensure the existence of democratic culture in the public service system.